Exploring the feasibility of content analysis in understanding international cooperation in APEC - Francis Mark A. Quimba; Mark Anthony A. Barral (Philippine Institute for Development Studies (PIDS), 2020)
International relations is considered an important aspect in the development of an economy and of a region by providing them opportunities to work together to address economic, social, political issues, environmental, and security issues. It allows economies to share information, technology, and best practices that can help them progress together. Such cooperation is realized through the participation and commitments in regional blocs, such as the Asia Pacific Economic Cooperation (APEC), where cooperation comes in many forms. Exploring the patterns of such cooperation provides an understanding of how APEC has evolved. It may highlight the achievements and learn from shortcomings. Also, exploring patterns of such cooperation provides direction APEC may take in the next decades. The quality of cooperation may also reveal how member economies have fared so far in their participation, as well as their economic or political stance on certain issues. To do such analysis, however, it must be noted that there are pieces of information that cannot be easily discerned by quantitatively analyzing available structured data. Analyzing cooperation may require a different type of methodology. This paper, therefore, explores the concepts and potential uses of content analysis in understanding international cooperation.
Keywords: 330; content analysis; text analysis; international cooperation